INTEGRALISTIK-INTERKONEKTIF PENDIDIKAN SALAF DAN KHALAF PONDOK PESANTREN TEBUIRENG JOMBANG - Walid, Moch. Khoirul (Rabbani: Jurnal Pendidikan Agama Islam, 2021)
Along with the development of the education system in Indonesia, pesantren are classified into two parts, namely the Salafi pesantren (pesantren that maintains classical traditions) and the Khalafi pesantren (pesantren that incorporate general knowledge or open school institutions). Not all educational institutions have integrated relationships with other knowledge, but from several Islamic boarding schools, there are many that have integrated salaf and khalaf education, such as the one in Pondok Pesantren Tebuireng Jombang. Keywords : Education, Integrated, Islamic boarding school